2017
DOI: 10.1002/app.45686
|View full text |Cite
|
Sign up to set email alerts
|

A dual‐induced self‐expandable stent based on biodegradable shape memory polyurethane nanocomposites (PCLAU/Fe3O4) triggered around body temperature

Abstract: Concerning the occurrence of in‐stent restenosis and stent thrombosis of stent implantation with balloon angioplasty, a dual‐induced self‐expandable stent based on biodegradable shape memory polyurethane nanocomposites (PCLAU/Fe3O4) was developed. The stent could maintain its temporary shape at body temperature for a certain period of time while it was able to recover to its permanent shape at the temperature a little above body temperature (around 40 °C) in both a water bath and an alternating magnetic field.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Biodegradable PUs have recently attracted much attention due to concerns about environmental accumulation and the need to develop new materials for biomedical applications[583][584][585]. For such PUs, the macrodiols (polymers or copolymers) or ChExs used are based on ingredients that are inherently biodegradable, such as: PCL[456,474,478,543,, PLA[598,601,605,606,608,[616][617][618][619][620][621], plant oils…”
mentioning
confidence: 99%
“…Biodegradable PUs have recently attracted much attention due to concerns about environmental accumulation and the need to develop new materials for biomedical applications[583][584][585]. For such PUs, the macrodiols (polymers or copolymers) or ChExs used are based on ingredients that are inherently biodegradable, such as: PCL[456,474,478,543,, PLA[598,601,605,606,608,[616][617][618][619][620][621], plant oils…”
mentioning
confidence: 99%
“…This behavior is similar to some other studies. For example, Gu et al reported that mechanical properties of biodegradable SMPU were improved with the addition of Fe 3 O 4 to 6 wt.% filler, and an opposite effect was observed at higher content.…”
Section: Resultsmentioning
confidence: 99%
“…Since systemic release is minimal compared to taking these medicines, the risk of toxicity is reduced . Another approach is to fabricate stents out of biodegradable materials as an alternative to permanent stents, because stents are only needed temporarily and the presence of a stent strut may cause long‐term complications such as late thrombosis (Figure a, second right) . There has been a first attempt of the patient‐specific customization of biodegradable stents using 3D imaging and 3D printing technology (Figure b, left) .…”
Section: Soft Bioelectronics–assisted Therapymentioning
confidence: 99%